2019
DOI: 10.3390/ani10010050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pair Versus Individual Housing on Performance, Health, and Behavior of Dairy Calves

Abstract: The aim of this study was to evaluate the effects of pair versus individual housing on performance, health, and behavior of dairy calves. Thirty female Holstein dairy calves were assigned to individual (n = 10) or pair housing (n = 10 pairs). The results showed that both treatments had a similar starter intake and average daily gain (ADG) during the preweaning period. During weaning and postweaning periods, paired calves had a higher starter intake, and the ADG of paired calves continued to increase but calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
7
18
0
1
Order By: Relevance
“…Our finding that the occurrence of diarrhea did not differ significantly between INDI and PH calves is consistent with 4 other studies (Chua et al, 2002;Jensen and Larsen, 2014;Pempek et al, 2016;Bolt et al, 2017) and partially in contrast with Liu et al (2019), who found an increase in the occurrence of diarrhea in pair-housed calves during wk 3. As discussed by the authors of the latter study, there is not enough evidence to support a diarrhea-increasing effect of pair housing, and thus the higher incidence of diarrhea in pair housing during wk 3 was likely due to low immunity to infection of calves aged from 2 to 4 wk and individual differences (Liu et al, 2019). Our finding, that diarrhea occurred more often in calves entering the experiment at earlier ages agrees with this well-established fact found in previous studies (Uetake, 2013;Cho and Yoon, 2014).…”
Section: Healthsupporting
confidence: 93%
See 4 more Smart Citations
“…Our finding that the occurrence of diarrhea did not differ significantly between INDI and PH calves is consistent with 4 other studies (Chua et al, 2002;Jensen and Larsen, 2014;Pempek et al, 2016;Bolt et al, 2017) and partially in contrast with Liu et al (2019), who found an increase in the occurrence of diarrhea in pair-housed calves during wk 3. As discussed by the authors of the latter study, there is not enough evidence to support a diarrhea-increasing effect of pair housing, and thus the higher incidence of diarrhea in pair housing during wk 3 was likely due to low immunity to infection of calves aged from 2 to 4 wk and individual differences (Liu et al, 2019). Our finding, that diarrhea occurred more often in calves entering the experiment at earlier ages agrees with this well-established fact found in previous studies (Uetake, 2013;Cho and Yoon, 2014).…”
Section: Healthsupporting
confidence: 93%
“…We failed to find a significant difference in solid feed intake in the INDI and PH calves. This result is in accordance with some studies (Chua et al, 2002;Pempek et al, 2013;Bolt et al, 2017;Liu et al, 2019), but in contrast with others (De Paula Vieira et al, 2010;Costa et al, 2015;Jensen et al, 2015;Pempek et al, 2016;Whalin et al, 2018) that found increased solid feed intake in pair-housed calves. We also failed to find a significant difference in growth of INDI and PH calves.…”
Section: Feed Intake and Growthsupporting
confidence: 93%
See 3 more Smart Citations